2020
DOI: 10.1089/ars.2018.7716
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Reactive Oxygen Species Inhibit IL-17A+ γδ T Cells and Innate Cellular Responses to Bacterial Lung Infection

Abstract: Aims: Excessive reactive oxygen species (ROS) are detrimental to immune cellular functions that control pathogenic microbes; however, the mechanisms are poorly understood. Our aim was to determine the immunological consequences of increased ROS levels during acute bacterial infection. Results: We used a model of Streptococcus pneumoniae (Spn) lung infection and superoxide dismutase 3-deficient (SOD3 -/-) mice, as SOD3 is a major antioxidant enzyme that catalyses the dismutation of superoxide radicals. First, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Cells were further stained with an antibody cocktail that contained FITC‐CD45, PE‐Siglec F, APC‐F4/80, eFluor 450‐CD11b, PE/Cy7‐CD11c, PerCp/eFluor710‐Ly6G (all from Life Technologies, USA) and analysed on a BD FACSAria. A strict gating strategy was used to exclude cell debris and cell aggregates and subset macrophage populations as previously described (Abdulnour et al, 2016; Anthony et al, 2020). Briefly, CD11b and CD11c were used to differentiate three distinct lung macrophage populations including resident alveolar macrophages (AM; CD45 + F4/80 + SSc High CD11c High CD11b − ), exudative macrophages (ExMacs; CD45 + SSc High F4/80 + CD11c High CD11b + ) and infiltrating monocytes (monocytes; CD45 + SSc High F4/80 + CD11c Low CD11b + ).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were further stained with an antibody cocktail that contained FITC‐CD45, PE‐Siglec F, APC‐F4/80, eFluor 450‐CD11b, PE/Cy7‐CD11c, PerCp/eFluor710‐Ly6G (all from Life Technologies, USA) and analysed on a BD FACSAria. A strict gating strategy was used to exclude cell debris and cell aggregates and subset macrophage populations as previously described (Abdulnour et al, 2016; Anthony et al, 2020). Briefly, CD11b and CD11c were used to differentiate three distinct lung macrophage populations including resident alveolar macrophages (AM; CD45 + F4/80 + SSc High CD11c High CD11b − ), exudative macrophages (ExMacs; CD45 + SSc High F4/80 + CD11c High CD11b + ) and infiltrating monocytes (monocytes; CD45 + SSc High F4/80 + CD11c Low CD11b + ).…”
Section: Methodsmentioning
confidence: 99%
“…Further exploring the function of mitochondria, we observed differential levels of mitoROS in γδT17 and γδT1 cells. It has been reported that excessive ROS inhibits lung γδT17 cells ( 47 ). We observed a lower level of mitoROS intrinsically in γδT17 cells, while γδT1 cells have higher levels of mitoROS, which may be related to their antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a reduction in the phagocytic capacity could contribute towards bacterial outgrowth in the lower airways and may in part underpin why asthmatics have a heightened risk of developing pneumococcal pneumonia (Jounio et al, 2010;Castro-Rodriguez et al, 2020). Pneumococcal infection in mice results in the robust recruitment of monocytes at day 2 post infection under the direction of the CCL2 chemokine, which enhances the killing of pneumococcus (Winter et al, 2007;Anthony et al, 2020). This recruitment is necessary to replenish local macrophage pools because SPN can induce apoptosis of resident macrophages to enhance pneumococcal killing (Aberdein et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal infection in mice results in the robust recruitment of monocytes at day 2 post infection under the direction of the CCL2 chemokine, which enhances the killing of pneumococcus ( Winter et al, 2007 ; Anthony et al, 2020 ). This recruitment is necessary to replenish local macrophage pools because SPN can induce apoptosis of resident macrophages to enhance pneumococcal killing ( Aberdein et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%